Effectiveness of Hematoma Block in Acute Pain Management and Closed Reduction of Fractures in Children Presenting to DHQ Kohat: An Exploratory RCT - Tauseef Raza, Abdul Munaf Saud, Shaukat Hayat Khan, Bakhat Hussain, Syed Abdur Rub Abidi, Ali Raza, Khalid Rehman (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Extremity fractures are common in children, particularly involving the lower segments of limbs, causing significant pain and anxiety. Adequate pain management is crucial during treatment. Methods: An exploratory randomized controlled trial study, between October 2019 and January 2020, compared hematoma block (HB) and intravenous analgesia (IVA) for pain management and closed reduction of simple extremity fractures in children. Two groups (64 children each) with forearm and shin bone fractures were randomly assigned HB or IVA. Pain levels were assessed using the visual analog scale before and after closed reduction at 5, 15, and 30 minutes. Fracture reduction quality was evaluated using X-rays. Results: Most fractures occurred in 8.5-year-old boys. HB resulted in significantly greater pain reduction compared to IVA, with continued improvement over time. Both methods achieved successful fracture reduction, but HB showed superior improvements in X-ray parameters such as angulation, shortening, and cortical apposition. Guidelines for pediatric forearm and shin bone fracture treatment in emergency settings were proposed based on X-ray parameters. Conclusion: Hematoma block emerges as a superior choice for pain management and closed reduction of pediatric forearm fractures, especially in resource-limited settings. Its efficacy in reducing pain and achieving better fracture alignment, as evidenced by X-ray parameters, supports its recommendation as a primary method in managing pediatric extremity fractures. Keywords: Extremity fractures, Pediatric pain management, Hematoma block, closed reduction